(3GdHfhc GdEdcJQhfjIs - (3efjQ eMeO(B, (3GdLfHjgis ((3GdEScfOQjI(B:s (3OGQ GdacQ GdLGeYj(B,s, 2006)
(3GdHfhc GdEdcJQhfjI(B-(3eRGjG GdHfhc GdEdcJQhfjI(B- (3eNGWQ GdHfhc GdEdcJQhfjI(B- (3eHGOF EOGQI GdeNGWQ(B- (3GdWHjYI GdbGfhfjI ddHfhc GdEdcJQhfjI(B- (3GdYedjGJ GdeUQajI GdEdcJQhfjI GdJj Jbhe HgG GdHfhc GdEdcJQhfjI(B- (3GdJMhdGJ GdeGdjI GdEdcJQhfjI GdJj jbhe HgG GdHfc GdeQcRj(B- (3eGgjI GdGehGd GdeJOGhdI dOi GdHfhc GdEdcJQhfjI(B- (3GdWHjYI GdbGfhfjI ddHjGfGJ GdEdcJQhfjI GdeJOGhdI ajeG Hjf GdHfc GdEdcJQhfj hYedGFg(B- (3GdJhbjY GdEdcJQhfj ddYedGA hMLjJg aj GdEKHGJ dOi GdHfhc GdEdcJQhfjI(B- (3NVhY GdHfhc GdEdcJQhfjI ddVQGFH(B.s
(3GdeQGLY U(B.251s
Keywords: (3GdHfhc GdEdcJQhfjIs; (3GdHfhc(B- (3eYGdLI GdHjGfGJ EdcJQhfjGs